Universality of light thermalization in multimoded nonlinear optical systems - Qi Zhong; Fan O. Wu; Absar U. Hassan; Ramy El-Ganainy; Demetrios N. Christodoulides (Nature Communications, 2023)
The origin of the Rayleigh–Jeans distribution associated with light thermalization in optical thermodynamic multimode nonlinear settings is discussed. Here the authors show that due to entropy maximization, this process is universal and is independent of the intricacies of the nonlinearities involved.